Factor Analysis Of Factors Driving Interest In Studying In Taiwan - Asmirin Noor; Andrean Sugianto (International Journal of Economics, Business and Innovation Research, 2025)
This research investigates the factors influencing students' interest in pursuing higher education in Taiwan. Utilizing factor analysis, the study identifies key components that significantly impact the decision-making process of prospective international students. The analysis reveals that out of eight identified factors, only two—Factor 1 and Factor 7—adequately represent the overall decision-making influences. Factor 1 encompasses variables such as Learning Facilities, Involvement in the International Arena, Industry Involvement, Satisfaction of International Students, Alumni Connections, Presence in Exhibitions, and Digital Campaigns. Meanwhile, Factor 7 includes Scholarship Programs and the Number of Research and Publications. Among these, the Quality of Campus Life emerges as the most dominant factor, with a very strong extraction value of 0.859. The study concludes that these factors collectively shape the attractiveness of Taiwan as a study destination, with the remaining 28 variables also exerting a significant influence, evidenced by their extraction values exceeding 0.5 on average.